2012
DOI: 10.1080/00207543.2011.625050
|View full text |Cite
|
Sign up to set email alerts
|

An innovation funnel process for set-based conceptual design via DOE exploration, DEA selection and computer simulation

Abstract: This paper presents a conceptual design approach including pattern creation from designers, alternative exploration with a DOE matrix, alternative analysis via computer simulation and alternative selection by DEA analysis. Designers possessing domain knowledge create various design patterns to meet the requirements of product performance and customer expectations. Then, based on these design patterns, the alternatives, considered as decision-making units (DMUs), are extracted from various quality level combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A suitable knowledge environment is important to have effective application of SBCE. The literature attempted to address knowledge provision through one of the following; database (Al-Ashaab et al, 2014;Essamlali et al, 2017;Wang and Terpenny, 2003;Wasim et al, 2013), knowledge base (Jeang and Liang, 2012;Malak et al, 2009), and case-based reasoning (CBR). A limited amount of research has been conducted on software system development by which to facilitate the application of SBCE.…”
Section: Knowledge Environment In Sbcementioning
confidence: 99%
“…A suitable knowledge environment is important to have effective application of SBCE. The literature attempted to address knowledge provision through one of the following; database (Al-Ashaab et al, 2014;Essamlali et al, 2017;Wang and Terpenny, 2003;Wasim et al, 2013), knowledge base (Jeang and Liang, 2012;Malak et al, 2009), and case-based reasoning (CBR). A limited amount of research has been conducted on software system development by which to facilitate the application of SBCE.…”
Section: Knowledge Environment In Sbcementioning
confidence: 99%
“…30 From a review of these techniques, Taguchi's orthogonal array approach was selected as it offered the opportunity to reduce the variance in the average cost. Previous research has shown that how the Taguchi method has been used to improve the quality characteristics of products; [31][32][33][34] this article does not focus on improving the quality of the product; however, the aim was to utilise these techniques to improve the quality of the average cost. Quality in this article is defined as reducing the variance in the cost estimate while optimising the product specification.…”
Section: Research Hypothesismentioning
confidence: 99%
“…Our approach to deal with the resource allocation and target setting problem is based on the data envelopment analysis (DEA) methodology, which has been studied for a long time. DEA, first introduced by Charnes et al (1978) and further developed by Banker et al (1984), has proved to be a preferable method for organization performance evaluations and has been applied to many disciplines since its inception (Emrouznejad et al, 2008;Jeang and Liang, 2012). Although DEA was initially proposed for the purpose of performance evaluation, the empirical analysis of operating status by DEA can provide some valuable insights for resource allocation (Lu and Hung, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Beasley (2003) proposed another perspective to allocating the fixed cost, one which maximizes the overall post-allocation efficiency scores with a set of common weights. The underlying logic of common weights is that the traditional DEA methods have used extreme points to compare one DMU to the rest of the sample set (Jeang and Liang, 2012), with weights being chosen to favor the evaluated DMU, while the common weights concept approaches the evaluation process by favoring all DMUs equally. Cook and Zhu (2005) further extended the Cook and Kress (1999) approach to the output orientation and proposed an executable method in the multi-input and multi-output case.…”
Section: Introductionmentioning
confidence: 99%